New insights on Lower Ordovician (Floian) reefs from the Argentine Precordillera: Biostratigraphic, sedimentologic and paleogeographic implications - Mestre García, Ana Isabel (2020)
The shallow carbonate facies of the middle part from the San Juan Formation that outcrops in the Central Precordillera is studied in the present contribution in order to assess conodont biostratigraphy and sedimentology. Three facies and five microfacies were recognized in the Niquivil and Talacasto sections. These facies represent three genetically-related depositional facies from distal to proximal, and include from shallow subtidal facies below wave action to shoal and reef facies. This reef and shoal facies is recorded for the first time at the Talacasto section. The reef framework consists mainly of calcimicrobes in consortia with pulchrilaminids, calathids and lithistid sponges conforming a microbial-metazoan matrix-supported reef. The pulchrilaminid Zondarella communis Keller and Flügel, present in these reef facies, is here assigned for first time to the late Floian (Early Ordovician), Oepikodus intermedius conodont Zone. In this sense, the Precordilleran reefs represent the latest Floian record of pulchrilaminids compared to the worldwide records for these Early Ordovician reef-builder organisms. This provides crucial information for understanding the dispersal pathways of these organisms, and allows a paleogeographic reconstruction of the western margin of Gondwana in the Early Ordovician.